Time-resolved optical absorption microspectroscopy of magnetic field sensitive flavin photochemistry - Antill, L.; Beardmore, Josh; Woodward, J. (American Institute of Physics, 2018)
The photochemical reactions of blue-light receptor proteins have received much attention due to their very important biological functions. In addition, there is also growing evidence that the one particular class of such proteins, the cryptochromes, may be associated with not only a biological photo-response but also a magneto-response, which may be responsible for the mechanism by which many animals can respond to the weak geomagnetic field. Therefore, there is an important scientific question over whether it is possible to directly observe such photochemical processes, and indeed the effects of weak magnetic fields thereon, taking place both in purified protein samples in vitro and in actual biochemical cells and tissues. For the former samples, the key lies in being able to make sensitive spectroscopic measurements on very small volumes of samples at potentially low protein concentrations, while the latter requires, in addition, spatially resolved measurements on length scales smaller than typical cellular components, i.e., sub-micron resolution. In this work, we discuss a two- and three-color confocal pump-probe microscopic approach to this question which satisfies these requirements and is thus useful for experimental measurements in both cases.